Mathematics Problem Solving Analysis on Higher Order Thinking Skills Based on Story Questions - Teguh Santoso; Mokhammad Dedi Penta Putra; Gilang A. Sandy; Dwi Priyo Utomo (International Journal of Learning Reformation in Elementary Education, 2022)
This study aims to determine the problem-solving ability of field independent (FI) and field dependent (FD) students in solving HOTS story problems. This type of research is qualitative research. The research strategy used is a descriptive model. This research was carried out at a junior school in Malang, Indonesia. The respondent was tenth-grade students. Data collection methods in this study include tests and interviews. Data analysis techniques include data collection, reduction, presentation, and concluding. The results of this study show that FI and FD students understand the problem. There is no difference between the two; FI and FD students are good at understanding the problem. FI students plan solutions well and can correctly create mathematical models, while FD students have difficulty developing mathematical models. In getting answers, FI and FD students have something in common: they are not quite right in the final solution.